Micro DBD plasma actuators for flow separation control on a low pressure turbine at high altitude flight operating conditions of aircraft engines. (5th March 2017) - De Giorgi, Maria Grazia; Ficarella, Antonio; Marra, Fedele; Pescini, Elisa
Highlights: Flow separation control over LPT suction surface was numerically investigated. Different PA configurations were compared. Micro PA outperformed the macro PA configuration. Micro DBD and micro L-PSJ with thrust vectoring suppressed completely separation. L-PSJ with thrust vectoring outperformed L-PSJ without thrust vectoring. Abstract: The present study aims to investigate, by numerical simulations, the potentiality of alternate current (AC) driven plasma actuators to reattach the separated flow along a low pressure turbine blade operating at low-Reynolds number. The flow over a curved wall plate, installed in a wind tunnel, to simulate the suction surface of a low-pressure turbine blade, was examined. Different plasma actuator geometries have been studied: a macro single dielectric barrier discharge (SDBD), a micro SDBD and a micro linear plasma synthetic jet (L-PSJ) without and with thrust vectoring. Numerical simulations were performed in absence and in presence of actuation. In presence of actuation, the plasma induced force was modelled and introduced as a source term in the momentum Navier-Stokes equation. The numerical flow simulations were validated with the experimental data. To compare the different plasma actuator geometries effects, the velocity profiles have been considered. The micro SDBD and the micro L-PSJ with thrust vectoring led to a reduction of recirculation and a substantial decrease of the boundary layer thickness. The reattachment of the flow was also evident by analyzing the wall shear stress profiles and the vortical flow structure using the Q-criterion. The characteristics of the boundary layer (shape factor, displacement and momentum thickness) in presence of the different actuation techniques were also studied.